Risk of surgical site infection in paediatric herniotomies without any prophylactic antibiotics - كوريه برديصان; علي وجيه; عمران عمار (Latakia University Journal -Medical Sciences Series, 2022)
Background and Aim of the study: The objective of this study is to evaluate whether the use of perioperative prophylactic antibiotics has an effect to prevent surgical site infection in paediatric herniotomy. Methods:A total of 125 children (92 males, 33 females) paediatric patients who underwent elective herniotomy were enrolled in this study; after excluding 14 cases (8 for having an antibiotic treatment within a week of surgery and 6 for having of chronic diseases). This study was conducted in Pediatric Surgery division at Tishreen University Hospital in Lattakia between 2019 and 2021. Through the use of random distribution, the research sample was distributed to two groups: Group A (62 children, or 49.6%, who did not use prophylaxis antibiotics) and Group B ( 63 children, 50.4%, who used antibiotics). .Results: The rate of SSI in the research sample was 5.4 with an average of 6 patients It ranged between 6.3% in group A (non-users of prophylactic antibiotics) and 3.2% in group B (patients who took prophylactic antibiotics). Not to mention that 5 of the 6 cases were superficial infections and were cured by follow-up with topical dressings without the need to use antibiotics. There were no statistically significant differences between groups A and B with regard to age, sex or weight according to the incidence of sepsis. With regard to the type of surgical suture used, as well as the duration of the operation or the length of the incision, it was noted that there was no significant differences in Statistic. Conclusion : Based on the result of this study, it may be concluded that antibiotic prophylaxis is not necessary for herniotomies in the paediatric age group.